PREOPERATIVE FACTORS INFLUENCING VISUAL RECOVERY AFTER VITRECTOMY FOR MYOPIC FOVEOSCHISIS. Issue 3 (March 2019) - Lehmann, Mathieu; Devin, François; Rothschild, Pierre-Raphael; Gaucher, David; Morin, Bruno; Philippakis, Elise; Massin, Pascale; Couturier, Aude; Tadayoni, Ramin
Abstract : Purpose: To determine the preoperative factors influencing visual recovery after vitrectomy for myopic foveoschisis. Methods: Sixty-six eyes of 65 consecutive patients operated on for myopic foveoschisis were retrospectively included. All eyes underwent a preoperative ocular examination including best-corrected visual acuity (BCVA) and spectral domain optical coherence tomography with central foveal thickness measurement and foveal status classification: simple foveoschisis, foveal detachment, or macular hole. To study the impact of preoperative visual acuity, 4 visual acuity groups separated by quartile ranges were defined. Postoperative visits at 1, 3, or 12 months including BCVA measurement and optical coherence tomography were recorded. Results: Mean refraction was −15.90 diopters, mean axial length was 30.30 mm, mean central foveal thickness was 590 μ m, and mean baseline logarithm of the maximum angle of resolution visual acuity was 0.68 (Snellen equivalent of 20/96). The final BCVA improved significantly from 3 months after surgery until the last follow-up visit; the mean logarithm of the maximum angle of resolution visual acuity at last follow-up was 0.43 (Snellen equivalent of 20/54). Mean central foveal thickness decreased significantly as soon as the first postoperative month ( P < 0.0001). The preoperative BCVA was the only independent factor significantly correlated with the final BCVA as opposed to the foveal status ( P < 0.0001). The mean BCVA and mean visual gain at the last follow-up visit were significantly different between the four visual acuity groups ( P < 0.0001 and P = 0.017, respectively). Conclusion: The main factor influencing the postoperative visual acuity is the preoperative visual acuity. Although the preoperative anatomical status seemed important in surgeon decision making, once normalized on visual acuity, it no longer influenced the postoperative visual acuity. Abstract : This study addresses the question of the preoperative factors after vitrectomy for high myopic patients presenting with a foveoschisis. Given this rare disease and the complexity of its surgery, the operative timing has never been clearly identified.